Ampicillin inhibition effect on HCT116 cell line - Thifaf Jassim Mohammed; Israa N.A. Al-Ibadi (Al-Qadisiyah Journal of Pure Science, 2018)
Ampicillin is a common antibiotic used treat infections derived by gram negative and positive bacteria. The hypothesis of this work is to uncover the therapeutic action of Ampicillin in case of human colorectal carcinoma as a model of gastric malignancy in the presence or absence of bacterial toxin. The results indicated that HCT116 viability was significantly attenuated by relatively high doses of Amp in presence or absence of LPS. However LPS treatment alone of high impact on HCT116 cells growth. We conclude that Ampicillin may have therapeutic effect on colorectal cancer upon and lower intestine bacterial infection. Further    studies required revealing Ampicillin effect on normal intestinal cells and underneath molecular mechanisms